Numerical simulation of carbon dioxide injection into a depleted hydrocarbon deposit - Marat Kamilovich Khasanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
Now underground utilization of the carbon dioxide worked out by industrial facilities is one of directions of solving the problem of prevention of further increase in greenhouse gas concentration in the Earth's atmosphere. At the same time the safest and the most reliable method of prevention of greenhouse gas exit to the surface is their conversion into the gas hydrate state, which allows storing the huge amount of gas in the small volume and at low pressures. The aim of the work is the theoretical research of hydrodynamic and thermophysical processes at underground utilization of greenhouse gases in the gas hydrate state. Based on the methods of mechanics of continuous medium the author has built the mathematical model of carbon dioxide injection in a natural layer, saturated with the water and methane in the initial state, followed by hydrate formation. For the case of injection of the warm carbon dioxide (with the temperature exceeding the initial temperature of the layer) the author constructed the self-similar solutions of the plane-rational task describing dynamics of temperature and hydrodynamic fields in the layer. As a result of numerical calculations it was determined that formation of carbon dioxide gas hydrate can happen both on the frontal surface, and in the extended zone. The author defined the limiting values of the mass flow rate of carbon dioxide injection, corresponding to occurrence of an extended gas hydrate formation zone. It is shown that the mode with formation of gas hydrate in extended area is implemented at small values of mass flow rate of injection, as well as at high values of permeability and initial water saturation of layer. Implementation of the mode with extended area of hydrate formation in layers with high values of permeability and initial water saturation, and also at small values of the mass flow rate of injection is caused by the fact that under existing conditions the pressure on phase transitions border is below the equilibrium pressure of formation of carbon dioxide gas hydrate corresponding to the temperature on this border.